Spectrophotometric Determination of Ruthenium Utilizing its Catalytic Activity on Oxidation of Hexacyanoferrate(II) by Periodate Ion in Water Samples - Srivastava, Abhishek; Sharma, Vivek; Prajapati, Anjali; Srivastava, Neetu; Naik, R. M. (Видавництво Львівської політехніки, 2019)
Для визначення рутенію(III) на мікрорівні застосовано каталітичний ефект хлориду рутенію на зов- нішнє перенесення електронів гексаціаноферрату(II) періодат- ним йоном у водному лужному середовищі. Встановлено оптимальні умови реакції та необхідний час. Лінійна залежність між поглинальною здатністю та концентрацією Ru(III) використана для визначення слідів Ru(III). Показано, що додавання інтерферентних йонів (в концентраціях, до 71 разів вищих за концентрацію Ru) істотно не впливає на ката- літичну активність Ru(III) при окисненні гексаціано- феррату(II) періодатним йоном. Поліамінокарбоксилати пригнічують його каталітичну здатність до максимального значення, якщо допустима межа є більшою за 14,29. Враховуючи відтворюваність, стабільність та селективность цього методу, запропоновано використовувати його для різних типів зразків води для визначення рутенію(III) на мікрорівні.

The catalytic effect of ruthenium chloride on the outer sphere electron transfer of hexacyanoferrate(II) by periodate ion in aqueous alkaline medium has been effectively employed to determine ruthenium(III) at micro level. The optimum reaction condition has been established and fixed time procedure is adopted. A linear relationship between changes in absorbance and added Ru(III) concentration has been utilized for the trace level determination of Ru(III). The results reveal that the addition of interfering ions (up to 71 times higher concentration of Ru) does not have significant effect on the catalytic activity of Ru(III) on oxidation of hexacyanoferrate(II) by periodate ion. Polyaminocarboxylates (HEDTA, EDTA and IDA) suppress its catalytic power to maximum, if tolerance limit is more than 14.29 times. Due to the reproducibility, stability and selectivity, this method can also be quantitatively applied in different types of water samples for determination of ruthenium(III) at micro level.
Спектрофотометричне визначення рутенію з використанням його каталітичної активності на окиснення гексацианоферрата(II) періодатним йоном в зразках води
Keywords: кінетика; механізм; гексаціаноферрат(II); періодат; рутеній(III); kinetics; mechanism; hexacyanoferrate(II); periodate; ruthenium(III)